2023
DOI: 10.3390/diseases11020062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Hypertension in Hargeisa, Somaliland: A Hospital-Based Cross-Sectional Study

Abstract: Hypertension is the leading risk factor for cardiovascular diseases and represents a major public health challenge worldwide. There is a paucity of information regarding the hypertension status of adults in Somaliland. We aimed to assess the magnitude of, and factors associated with, hypertension among adult patients seeking care at Hargeisa group hospital in Hargeisa city, Somaliland. We conducted a health facility-based cross-sectional study enrolling adult outpatients. We used the World Health Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
3
0
0
Order By: Relevance
“…The highest odds of hypertension were observed among participants aged over 50 years. Furthermore, our findings indicated that male gender, history of khat consumption, and overweight status were associated with increased odds of hypertension, consistent with a study conducted in Hargeisa, Northern Somalia 10…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The highest odds of hypertension were observed among participants aged over 50 years. Furthermore, our findings indicated that male gender, history of khat consumption, and overweight status were associated with increased odds of hypertension, consistent with a study conducted in Hargeisa, Northern Somalia 10…”
Section: Discussionsupporting
confidence: 91%
“…The highest odds of hypertension were observed among participants aged over 50 years. Furthermore, our findings indicated that male gender, history of khat consumption, and overweight status were associated with increased odds of hypertension, consistent with a study conducted in Hargeisa, Northern Somalia 10 Similarly, the aforementioned study on hypertension in Hargeisa, Somalia, revealed associations between male sex, higher BMI, and advancing age with hypertension, consistent with findings from studies conducted in sub-Saharan Africa, which identified older age as strongly associated with hypertension. These observations are supported by scientific evidence indicating that as individuals age, they are more prone to developing hypertension due to increased vascular resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation